Pengaruh Teknik Stimulasi Puting Susu Terhadap Lama Persalinan Kala I - Sih Rini Handajani; KH Endah Widhi Astuti (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Nipple Stimulation, Labor Kala I. The purpose of this study was to determine the influence of nipple stimulation techniques of the duration of labor in the first stage in Puskesmas Gajahan Surakarta. This research is a quasi-experimental with posttest design with a control group. The population in this study is that maternal primigravid active phase of the first stage in the clinic Gajahan Surakarta. Samples were taken by accidental sampling technique. Based on the estimation formula of the samples obtained a total sample of 62 women giving birth. 31 maternal treated with nipple stimulation, while 31 as the control group with the mobilization of the left oblique. Data collection using observation sheet implementation nipple stimulation and sheets partograph to observe the first stage of labor longer active phase. The average length of the first stage of labor in the control group maternity primigravida who did nipple stimulation (mobilization) in Puskesmas Gajahan is 3:36 minutes, the average length of first stage of labor in the treatment group maternity primigravida who does nipple stimulation in Puskesmas Gajahan is 3:21 minutes and no influence of nipple stimulation to the first stage of labor longer with p-value = -0.295 (p <0.05), so Ho accepted because -0.295 <2.002. Nipple stimulation has an influence on the first stage in a long time Gajahan Surakarta Health Center.